Cognitive Impairment Occurs in Children and Adolescents With Multiple Sclerosis: Results From a United States Network. (January 2013) - Julian, Laura; Serafin, Dana; Charvet, Leigh; Ackerson, Joseph; Benedict, Ralph; Braaten, Ellen; Brown, Tanya; O'Donnell, Ellen; Parrish, Joy; Preston, Thomas; Zaccariello, Michael; Belman, Anita; et al.
In the largest sample studied to date, we measured cognitive functioning in children and adolescents with pediatric multiple sclerosis (n = 187) as well as those with clinically isolated syndrome (n = 44). Participants were consecutively enrolled from six United States Pediatric Multiple Sclerosis Centers of Excellence. Participants had a mean of 14.8 ± 2.6 years of age and an average disease duration of 1.9 ± 2.2 years. A total of 65 (35%) children with multiple sclerosis and 8 (18%) with clinically isolated syndrome met criteria for cognitive impairment. The most frequent areas involved were fine motor coordination (54%), visuomotor integration (50%), and speeded information processing (35%). A diagnosis of multiple sclerosis (odds ratio = 3.60, confidence interval = 1.07, 12.36, P = .04) and overall neurologic disability (odds ratio = 1.47, confidence interval = 1.10, 2.10, P = .03) were the only independent predictors of cognitive impairment. Cognitive impairment may occur early in these patients, and prompt recognition is critical for their care.